Pengaruh Pengungkapan Sustainability Report Terhadap Kinerja Keuangan Perusahaan yang Terdaftar di Daftar Efek Syariah (DES) Periode 2018-2022 - Hanif Fauziyah (Fakultas Ekonomi dan Bisnis, 2023)
Nowadays, financial conditions alone are not enough to ensure sustainable corporate value, the existence of social and environmental events experienced by several companies today is also one of the triggers for stakeholder demands. The phenomenon of increasing issues of natural damage reminds people of the importance of managing limited natural resources so that companies are required to be able to use them efficiently, especially in meeting their operating needs. Based on this phenomenon, this study was conducted to determine the effect of publishing sustainability reports on the company's financial performance. With 27 companies used as the sample, this research was conducted using multiple linear regression analysis method. The results of this study are: 1) Disclosure of sustainability reports in the economic dimension has a significant negative effect on financial performance as proxied by NPM, 2) Disclosure of sustainability report economic dimension has no significant effect on financial performance proxied by EPS, 3) Disclosure of sustainability report environmental dimension has a significant positive effect on financial performance proxied by NPM, 4) Disclosure of sustainability report environmental dimension has a significant positive effect on financial performance proxied by EPS, 5) Disclosure of sustainability report social dimension has no significant effect on financial performance proxied by NPM, 6) Disclosure of sustainability report social dimension has a significant negative effect on financial performance proxied by EPS.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: Sustainability report; GRI; financial performance; NPM; EPS.